2021
DOI: 10.1088/1755-1315/672/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Added value of robusta coffee products of “dwi tunggal” farmer group in bromo mountain slope

Abstract: Indonesia is among the four largest of coffee beans producing country in the world with production reaching more than half a million tons per year. Pasuruan Regency, located on the slopes of Mount Bromo, has a coffee plantation area of 4,458.20 hectares with a coffee production yield of 1,283.13 tons which has a very high potential of producing good quality Robusta coffee. This potential is used by farmer groups, mainly those under “Dwi Tunggal” farmer group association (Gapoktan) to produce Robusta roasted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…It is worth noting that the added value of roasted Excelsa coffee beans, as ascertained in this study, aligns closely with the added value observed in roasted Robusta coffee beans sourced from regions beyond Wonosalam, Jombang. Specifically, roasted Robusta coffee beans in Grabag, Magelang, yield an added value of IDR 16,000 per kilogram (Adji et al, 2021), while in the Kalipucang area, Pasuruan, this figure stands at IDR 33,871 per kilogram (Hidayanti et al, 2021). However, when juxtaposed with the added value of Arabica coffee beans cultivated in the Cisarua area, Bogor, Excelsa coffee's value addition in Wonosalam appears comparatively lower.…”
Section: B Income and Profitmentioning
confidence: 99%
“…It is worth noting that the added value of roasted Excelsa coffee beans, as ascertained in this study, aligns closely with the added value observed in roasted Robusta coffee beans sourced from regions beyond Wonosalam, Jombang. Specifically, roasted Robusta coffee beans in Grabag, Magelang, yield an added value of IDR 16,000 per kilogram (Adji et al, 2021), while in the Kalipucang area, Pasuruan, this figure stands at IDR 33,871 per kilogram (Hidayanti et al, 2021). However, when juxtaposed with the added value of Arabica coffee beans cultivated in the Cisarua area, Bogor, Excelsa coffee's value addition in Wonosalam appears comparatively lower.…”
Section: B Income and Profitmentioning
confidence: 99%
“…The added Value of agriculture can be improved through downstream activities in the form of agro-industry and agriculture-based services (Sobir et al, 2021). Hidayanti et al (2021) state that every business wants to get maximum profit with low production costs and an efficient level of production efficiency by calculating added Value. Value added is a fundamental concept that reflects the Value of profits obtained from processed products (finished materials) minus the Value of raw materials and production costs in addition to the intermediate expenses used in the process in kilograms of raw materials.…”
Section: Downstreammentioning
confidence: 99%
“…Beberapa market pasar kopi Robusta nasional mensyaratkan terpenuhinya standar yang tinggi tentang kualitas citarasa agar diterima sebagai pemasok (Hidayanti, 2021;Kuswardhani, 2019). Pekebun kopi apabila tidak mendapatkan edukasi dan training yang tepat akan mengakibatkan menurunnya kualitas citarasa kopi yang berujung pada rendahnya harga kopi Robusta di pasaran (Sarirahayu & Aprianingsih, 2018;Seeck & Diehl, 2017).…”
unclassified